The Effect of Finger Painting Activities on Raudhatul Atfal's Children's Creativity: Pengaruh Kegiatan Finger Painting Terhadap Kreativitas Anak Raudhatul Atfal - Risma Elfariyanti; Eni Fariyatul Fahyuni (Academia Open, 2022)
This research is motivated by the lack of creativity of children in RA Baitussalam Gempol. The low ability of children's creativity because teachers still use activities that do not attract children's interest. So the researchers tested finger painting activities on children's creativity to find out whether finger painting activities had an effect on children's creativity at RA Baitussalam Gempol. The type of this research used is experimental research with pretest-posttest design. The samples in this study were groups A1 and A2 using simple random sampling, where A2 was used as the experimental class with the treatment given, namely finger painting activities. Meanwhile, group A1 was used as the control class. The results of this study indicate that Sig (2-tailed) is 0.000 < 0.05 which means that Islamic finger painting activities have a significant effect on children's creativity at RA Baitussalam Gempol. Keywords - Finger Painting, Creativity.